Perlindungan Konsumen terhadap jual-beli Sepeda Motor di Facebook Marketplace menurut Hukum Dagang - Razkha Yudistira Adrian Farhan; Muhamad Fiqri Al Buchori; Muhammad Farid Dzulfikri; Muhammad Daffa Naufal Ihsan; Rafli Zaidan; Hilmy Abiyyu Taqy; Daniyal Kamil Amalushaleh; Zahran Abhipraya; Nandang Najmudin (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
Advances in information technology have driven an increase in e-commerce activity, including the buying and selling of motorcycles through Facebook Marketplace. The ease of access and wide market reach have made this platform widely used by a segment of the population. However, online transactions also pose various risks, such as fraud, discrepancies in the condition of goods, hidden defects, and a lack of legal certainty for consumers. In addition to online transactions, face-to-face transactions also carry risks that are no less significant, such as the possibility that a seller might bring accomplices to threaten the buyer into accepting a lower price or even resort to robbery accompanied by violence. This study aims to analyze the forms of legal protection provided to consumers in sales transactions on Facebook Marketplace specifically, the sale and purchase of motorcycles from the perspective of Indonesian commercial law. The research methods employed include a statutory approach and a conceptual approach. Data sources were derived from primary, secondary, and tertiary legal materials related to consumer protection, electronic transactions, and commercial law. The results of the study indicate that consumer protection in motorcycle sales transactions under commercial law is regulated by commercial law provisions, the Consumer Protection Act, and regulations pertaining to electronic transactions.